How EFL Learners Maintain Motivational Factors and Positive Attitudes during COVID-19 Pandemic: A Qualitative Study - Adara, Reza Anggriyashati; Puspahaty, Novita (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The present study aims to analyze how a group of EFL learners in Indonesia maintained their motivation and positive attitudes toward English learning during the Covid-19 pandemic. The present study applied a qualitative study by conducting semi-structured interviews with ten respondents. The results suggest that the Covid-19 pandemic has affected the respondents significantly. At the beginning of the Covid-19 pandemic, most respondents were demotivated but they were able to motivate themselves again by reminding themselves of the reasons they learned English in the first place. Those reasons are mostly dominated by extrinsic factors such as their need to get jobs, studying overseas and the benefits of mastering English for their future also motivated the respondents. However, some are still motivated to learn English because they are intrinsically motivated. The results suggest that both intrinsic and extrinsic motivation are needed to maintain learners' motivation and positive attitudes toward language learning. In addition, maintaining personal communication with students during tough times such as the Covid-19 pandemic seems important to be conducted by teachers. By keeping personal communication, teachers can help maintain students' motivation. Besides that, the findings of the present study indicate that the respondents used various methods to maintain their motivation such as using social media to learn English and constantly reminding themselves of their language learning goals. In regards to this, teachers should help students by integrating social media into the lessons and providing affirmations that remind students of the benefits of English language mastery.